ROLE OF STORYTELLING IN TEACHING ENGLISH (Conferencea, 2022)
For a long time, people have been using storytelling to communicate and share knowledge. Stories make any information easy for perception, so according to this fact, teachers can use the powerful teaching tool to achieve the main goal of getting their message across to students in a compelling way. Stories excite the imagination, evoke emotions, they serve to ensure that the listener is ready to receive information. As the American writer Gail Godwin says, “Good teaching is one third preparation and the rest theatre.” In this article, we will look at storytelling techniques that will help turn learning into an exciting activity, and make any learning concepts memorable